(3faGFS GdJPcQI aj TQM GdJHUQIs - (3GdZQGhj, eMeO QVG Hf bGSe Hf eMeO, J(B1385(3g`s ((3HNW GdeDdas)
(3ChdgG (B:s
(3GdHGH GdSGHY ef GdUdGI aj HjGf UdGI GdNha hCMcGegG (B...s
(3BNQgG (B:s
(3Ydi Cfg Qhj GSJMHGH aYd gPg GdJcHjQGJ YbjH cd UdGI(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B6(3,U(B128s
(3GdPQjYI(B:(3L(B24(3,Qbe(B1248s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis